Estimasi Debit Aliran Menggunakan Data Radar Cuaca (Studi Kasus : DAS Manna, Bengkulu) - HANDOYO, MUHAMMAD FAJAR (Stasiun Pemantau Atmosfer Global Bukit Kototabang, 2021)
Weather radar has an advantage in estimating rainfall, because it has a high spatial resolution (up to 0.5 km). Weather radar estimate rainfall can be used for various needs, including for hydrological modeling. This study aims to utilize the Bengkulu BMKG weather radar to estimate discharge of the Manna watershed in December 2018. The Z-R equation is determined based on radar reflectivity (Z) and observed rainfall (R) data. Weather radar data processing uses Wradlib software based on the Python programming language. The HEC-GeoHMS and HEC-HMS hydrological models were used to calculate the discharge based on the weather radar rainfall input. The Gridded Soil Conservation Service Curve Number (SCS CN) and ModClark methods are used to determine the method of loss and travel time required for water to the outlet point. Meanwhile, base flow and routing use Recession and Lag methods. As a result, the equation between weather radar reflectivity and observed rainfall is Z=2,65R1,3. The simulation discharge produces an RMSE value of 11.99 m3/second before calibration, and an RMSE of 4.37 m3/second after calibration. In addition, the rainfall forecasted by weather radar has the same pattern as the daily discharge fluctuation of the Manna watershed.